Application of enhanced recovery after surgery during the perioperative period in infants with Hirschsprung's disease – A multi-center randomized clinical trial. Issue 7 (July 2020) - Tang, Jie; Liu, Xiang; Ma, Tongshen; Lv, Xiaofeng; Jiang, Weiwei; Zhang, Jie; Lu, Changgui; Chen, Huan; Li, Wei; Li, Hongxing; Xie, Hua; Du, Chunxia; et al.
Summary: Background & aims: Various enhanced recovery after surgery (ERAS) guidelines have been established for several kinds of adult surgeries. While the guidelines for pediatric surgeries remained to be explored. The aim of the study was to prospectively evaluate the safety and efficacy of an ERAS protocol for Hirschsprung's disease (HSCR) infants undergoing pull-through procedures. Methods: An infant-specific ERAS protocol was developed and implemented at multiple centers from June 1, 2016 to December 31, 2017. The study included 145 consecutive patients who underwent pull-through surgery for HSCR in three Children's hospitals. Patients were primarily divided into three groups based on the clinical classification and surgical methods. Group I included patients with the short segment type who received transanal endorectal pull-through (TEPT) surgery. Group II comprised of patients with the classical type and long segment type who received laparoscopic-assisted pull-through (LAPT) surgery. Group III involved patients with the long segment type (who had received ileostomy or colostomy during the neonatal period) and total colonic aganglionosis who received open pull-through (OPPT) surgery. Patients in the three groups mentioned above were randomly and equally assigned into the ERAS group and traditional (TRAD) group with random number table row randomization. The primary outcome was the length of postoperative hospital stay (LOS). Secondary outcomes of interest included white blood cell (WBC) and C-reactive protein (CRP) on postoperative day 1 (POD 1), the blood glucose at the time of anesthesia and 24 h after surgery, time to first defecation, time to regular diet, plasma markers of nutrition status on POD 5, plasma natrium on POD 5, the mean intraoperative fluid volume, time to discontinuation of intravenous infusion, incidence of postoperative complications, re-admission within 30 days, hospitalization costs, parental satisfaction, and growth from admission to 6 months after surgery. Results: 73 and 75 patients were assigned to the TRAD and ERAS groups, respectively. There were no significant differences in demographic data. The LOS decreased from 9.5 days in the TRAD group to 7.9 days ( P  < 0.001) in the ERAS group. WBC count on POD 1 showed no significant difference between the two groups. CRP on POD 1 in the ERAS group was significantly lower ( P  < 0.001). In the ERAS group, the blood glucose was higher at anesthesia compared to the TRAD group ( P  < 0.001). On the contrary, the blood glucose at 24 h after surgery was significantly lower in the ERAS group ( P  < 0.001). Intraoperative fluid volume was lower in the EARS group ( P  < 0.001). ERAS could also reduce the time to first defecation ( P  < 0.001), discontinuation of intravenous infusion ( P  < 0.001) and regular diet ( P  < 0.001). In the ERAS group, the concentrations of prealbumin and retinol conjugated protein on POD 5 were higher than those in the TRAD group ( P  < 0.001, P  < 0.001, respectively). The plasma natrium had no difference in the two groups on POD 5 ( P  > 0.05). The rate of complications ( P  > 0.05) and 30-day re-admission ( P  > 0.05) were not significantly different between the two groups. Hospitalization costs were also reduced ( P  < 0.001). ERAS group has a higher parental satisfaction rate, although there was no statistical difference (96% vs 89%). There was no difference in growth between the ERAS and the TRAD groups from admission to 6 months after the surgery (weight for age z score: P  > 0.05, weight for length z score: P  > 0.05). We also found that the shortening of LOS by the application of ERAS protocol was more obvious in the OPPT group (−2.5 ± 1.0) than that in the TEPT (−1.9 ± 1.3) and LAPT (−1.3 ± 0.4) groups. Conclusions: Implementation of the ERAS protocol in infants undergoing HSCR pull-through operations is safe and efficient. The ERAS protocol is worthy of recommendation. Trial registration: Clinical Trials.gov identifier: NCT02776176 .